Gas Barrier Film

The gas barrier film, featuring a multi-layer polyethylene film structure with specific layers and a gas barrier layer containing inorganic oxides or coatings, addresses the challenges of processing stability, transparency, and heat resistance, ensuring effective gas barrier performance even after sterilization.

JP7658399B2Active Publication Date: 2025-04-08TOPPAN HOLDINGS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023122189
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-04-08
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

The challenge is to develop a gas barrier film with excellent processing stability, transparency, and heat resistance, particularly for use in packaging materials that require monomaterials and efficient recycling, while avoiding wrinkles and ensuring gas barrier properties are maintained after heating and sterilization.

Method used

A laminated gas barrier film structure comprising a multi-layer polyethylene film with a surface layer, intermediate layer, and back layer, where the surface layer is between the intermediate layer and the gas barrier layer, and the gas barrier layer includes an inorganic oxide layer or a gas barrier coating layer containing specific materials such as water-soluble polymers and metal alkoxides.

Benefits of technology

The solution provides a gas barrier film with enhanced processing stability, transparency, and heat resistance, ensuring the gas barrier properties are maintained even after heating and sterilization, thus meeting the demands for monomaterial packaging and efficient recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658399000007
    Figure 0007658399000007
  • Figure 0007658399000008
    Figure 0007658399000008
  • Figure 0007658399000009
    Figure 0007658399000009
Patent Text Reader

Abstract

To provide a gas barrier film having excellent processing stability, excellent transparency and excellent heat resistance.SOLUTION: A gas barrier film has a multilayer polyethylene film and a gas barrier layer, wherein the multilayer polyethylene film has a surface layer, an intermediate layer and a rear layer in this order, the surface layer is provided between the intermediate layer and the gas barrier layer, the surface layer is composed of a medium density polyethylene resin or a high density polyethylene resin having a density of 0.926 g / cm3 or more, composite elastic moduli of the surface layer and the rear layer are 1.45 GPa or more and less than 1.90 GPa, a composite elastic modulus of the intermediate layer is 1.80 GPa or more and less than 2.50 GPa, a ratio of the thickness of the intermediate layer to the total thickness of the surface layer and the rear face layer is 0.5 or more, a temperature indicated by a maximum layer of a melting peak of the multilayer polyethylene film is higher than 129°C and lower than 136°C, and the gas barrier layer has at least one of an inorganic oxide layer and a gas barrier coating layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gas barrier film. [Background technology]

[0002] Packaging materials used for packaging foods, medicines, etc. are required to have the property of preventing the intrusion of gases (water vapor, oxygen, etc.) that denature the contents (gas barrier properties) in order to prevent deterioration or spoilage of the contents and maintain their function and quality. In addition, packaging materials are required to have excellent heat resistance because they may be subjected to heat sterilization treatment such as boiling. For this reason, laminates (gas barrier films) that have gas barrier properties and heat resistance are used for these packaging materials.

[0003] As a gas barrier film, one in which a gas barrier layer made of a material having gas barrier properties is provided on the surface of a resin substrate is known. As a gas barrier layer, a metal foil, a metal vapor deposition film, a coating formed by a wet coating method, etc. are known. As a resin substrate, a polyolefin film such as a polyethylene film is known. For example, Patent Document 1 describes an aluminum vapor deposition polyethylene film characterized in that an aluminum vapor deposition film is provided on the surface of a non-oriented polyethylene film having a thickness of less than 30 μm and made of linear low-density polyethylene produced by using a metallocene catalyst.

[0004] Also, studies have been conducted to improve the properties of a gas barrier film by forming a resin substrate into a laminate having a plurality of resin layers. For example, Patent Document 2 describes a film capable of suppressing the occurrence of wrinkles, which comprises a resin layer including a first surface and a second surface, and a deposition layer provided on the second surface of the resin layer, and the resin layer has a density higher than that of the first layer constituting the first surface, and a density of 0.934 g / cm3. 3 and at least one hard layer having a density of at least 1000 nm, wherein the total thickness of the hard layers is at least 60% of the total thickness of the resin layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2001-179878 A [Patent Document 2] JP 2018-24213 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, due to growing environmental awareness triggered by the problem of marine plastic waste, there is a demand for more efficient sorting and recovery of plastic materials and recycling, and there is also a demand for mono-material packaging materials.

[0007] However, in conducting research in order to develop a mono-material gas barrier film, the inventors found that, depending on the type of polyethylene resin constituting each layer of the polyethylene film, wrinkles may occur on the surface of the polyethylene film, making it difficult to form a gas barrier layer or to impart sufficient transparency and heat resistance.

[0008] Therefore, one aspect of the present invention aims to provide a gas barrier film that has excellent processing stability when providing a gas barrier layer, excellent transparency, and excellent heat resistance that enables the gas barrier properties to be maintained even after heat sterilization treatment. [Means for solving the problem]

[0009] One aspect of the present invention includes the following [1] to [6]. [1] A gas barrier film having a laminated structure including a multilayer polyethylene film and a gas barrier layer, the multilayer polyethylene film has a surface layer, an intermediate layer, and a back layer in this order, the surface layer being provided between the intermediate layer and the gas barrier layer; The surface layer has a thickness of 0.926 g / cm 3 It is made of medium density polyethylene resin or high density polyethylene resin having a density of or above, The composite elastic modulus of the surface layer and the back layer is 1.45 GPa or more and less than 1.90 GPa, and the composite elastic modulus of the intermediate layer is 1.80 GPa or more and less than 2.50 GPa, The ratio of the thickness of the intermediate layer to the total thickness of the front layer and the back layer is 0.5 or more; The temperature at which the maximum melting peak is observed in differential scanning calorimetry of the multilayer polyethylene film is more than 129°C and less than 136°C, The gas barrier film, wherein the gas barrier layer comprises at least one of an inorganic oxide layer and a gas barrier coating layer. [2] The density of the multilayer polyethylene film is 0.940 g / cm 3 The gas barrier film according to [1] above. [3] The gas barrier layer has the inorganic oxide layer, The gas barrier film according to [1] or [2], wherein the inorganic oxide layer contains at least one of aluminum oxide and silicon oxide. [4] The gas barrier layer has the gas barrier coating layer, The gas barrier film according to any one of [1] to [3], wherein the gas barrier coating layer contains a water-soluble polymer and at least one member selected from the group consisting of metal alkoxides, their hydrolysates, and reaction products thereof. [5] The gas barrier layer has the gas barrier coating layer, The gas barrier film according to any one of [1] to [4], wherein the gas barrier coating layer contains at least one selected from the group consisting of a silane coupling agent, a hydrolysate thereof, and a reaction product thereof. [6] The gas barrier layer has the gas barrier coating layer, The gas barrier film according to any one of [1] to [5], wherein the gas barrier coating layer contains a polyvalent metal salt of a carboxylic acid. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide a gas barrier film that has excellent processing stability when providing a gas barrier layer, excellent transparency, and excellent heat resistance that enables the gas barrier property to be maintained even after heat sterilization treatment. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a cross-sectional view of a gas barrier film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a gas barrier film according to another embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of a gas barrier film according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiments of the present disclosure will be described in detail with reference to the drawings. Note that the drawings are schematic, and for example, the relationship between thickness and planar dimensions, and the ratio of thicknesses of each layer are different from the actual ones. In addition, the embodiments shown below are examples of configurations for embodying the technical idea of ​​the present disclosure, and the technical idea of ​​the present disclosure is not limited to the materials, shapes, structures, etc. of the components described below.

[0013] [Gas barrier film] 1 is a cross-sectional view of a gas barrier film according to one embodiment of the present invention. The gas barrier film 100 has a laminated structure including at least a multilayer polyethylene film 10 and a gas barrier layer 20.

[0014] The content of the polyethylene resin in the gas barrier film 100 may be 90% by mass or more, or 95% by mass or more, based on the total amount of the gas barrier film 100, from the viewpoint of realizing mono-materialization and excellent recyclability.

[0015] The thickness of the gas barrier film 100 may be 5 μm or more, 10 μm or more, or 15 μm or more from the viewpoint of easily achieving excellent heat resistance and easy stable production, and may be 100 μm or less, 60 μm or less, or 40 μm or less from the viewpoint of cost.

[0016] <Multi-layer polyethylene film> The multilayer polyethylene film 10 comprises a surface layer 11, an intermediate layer 12, and a back layer 13, in this order. The surface layer 11 is provided between the intermediate layer 12 and the gas barrier layer 20. The surface layer 11 and the back layer 13 are each the outermost layer of the multilayer polyethylene film 10.

[0017] The content of polyethylene resin in the multilayer polyethylene film 10 may be 90 mass % or more, or 95 mass % or more, based on the total amount of the multilayer polyethylene film 10, from the viewpoint of realizing mono-materialization and excellent recyclability.

[0018] The density of the multilayer polyethylene film 10 is set to 0.935 g / cm from the viewpoints of being less prone to wrinkles, being more stable in processing, and being more likely to maintain gas barrier properties and adhesion even after heat sterilization treatment, and being more heat resistant. 3 More than 0.940g / cm 3 More than 0.945g / cm 3 More than 0.950g / cm 3 or more than 0.955g / cm 3 The density of the multilayer polyethylene film 10 may be 0.980 g / cm or more. 3 Below, 0.975g / cm 3 Below, 0.970g / cm 3 Below, 0.965g / cm 3 or less than 0.960g / cm 3 It may be the following.

[0019] The multilayer polyethylene film 10 may be unstretched. The multilayer polyethylene film 10 being unstretched means that the absolute value of the molecular orientation degree of the multilayer polyethylene film is less than 1.07. When the multilayer polyethylene film 10 is unstretched (the absolute value of the molecular orientation degree is less than 1.07), the gas barrier layer 20 is less likely to peel off in the vicinity of the surface layer 11 of the multilayer polyethylene film 10, and the adhesion to the gas barrier layer 20 tends to be excellent. The absolute value of the molecular orientation degree means the absolute value of the molecular orientation degree of molecular chains in the plane of the multilayer polyethylene film measured by rotating the multilayer polyethylene film in a microwave polarized electric field using a microwave molecular orientation meter (e.g., MOA-5012A manufactured by Oji Measurement Instruments Co., Ltd.).

[0020] The thickness of the multilayer polyethylene film 10 is not particularly limited and can be appropriately determined according to the cost and application, taking into consideration the suitability as a packaging material and the suitability for lamination with other layers. The thickness of the multilayer polyethylene film 10 may be 3 μm or more, 5 μm or more, 6 μm or more, or 10 μm or more, or may be 200 μm or less, 120 μm or less, 100 μm or less, or 40 μm or less.

[0021] (surface) The surface layer 11 is 0.926 g / cm 3 The surface layer 11 is a layer made of a medium density polyethylene resin or a high density polyethylene resin having a density of 0.926 g / cm 3 By being made of the above medium density polyethylene resin or high density polyethylene resin, the multilayer polyethylene film 10 has excellent heat resistance. In this specification, high density polyethylene resin means a polyethylene resin having a density of 0.942 g / cm 3 Hereinafter, the polyethylene resin constituting the surface layer 11 will also be referred to as a first polyethylene resin.

[0022] The content of the first polyethylene resin in surface layer 11 may be 90 mass% or more, 95 mass% or more, or 98 mass% or more, or may be 100 mass% (an embodiment in which surface layer 11 is substantially composed of the first polyethylene resin) based on the total amount of surface layer 11. When surface layer 11 is composed of multiple polyethylene resins (for example, multiple polyethylene resins having different average molecular weights, densities, etc.), a mixture of the multiple polyethylene resins is used as the first polyethylene resin.

[0023] From the viewpoints of being less prone to wrinkles and having better processing stability, and of being more likely to maintain gas barrier properties even after heat sterilization treatment and having better heat resistance, the surface layer 11 may be composed of a first polyethylene resin having a density in the following range. The density of the first polyethylene resin is 0.930 g / cm 3 More than 0.935g / cm 3 or more than 0.940g / cm 3 The density of the first polyethylene resin may be 0.970 g / cm or more. 3 Below, 0.965g / cm 3 or less than 0.960g / cm 3 In particular, the density of the first polyethylene resin may be 0.960 g / cm or less. 3 By satisfying the above condition, the surface of the multilayer polyethylene film 10 can be prevented from becoming rough and resin powder can be prevented from being generated, making it easier to achieve excellent gas barrier properties.

[0024] The composite elastic modulus of the surface layer 11 is 1.45 GPa or more and less than 1.90 GPa. When the composite elastic modulus of the surface layer 11 is 1.45 GPa or more and less than 1.90 GPa, the transparency and gas barrier property of the multilayer polyethylene film 10 are excellent. The composite elastic modulus of the surface layer 11 can be measured by a nanoindentation method, specifically, by the method described in the examples below.

[0025] The composite elastic modulus of the surface layer 11 may be 1.50 GPa or more, 1.55 GPa or more, or 1.60 GPa or more, and may be 1.85 GPa or less, 1.80 GPa or less, or 1.75 GPa or less.

[0026] The melt flow rate MFR1 of the first polyethylene resin at 190°C and a load of 2.16 kg is not particularly limited and can be appropriately adjusted depending on the method for producing the first polyethylene resin. The melt flow rate MFR1 of the first polyethylene resin at 190°C and a load of 2.16 kg may be 5 g / 10 min or less, 3 g / 10 min or less, or 1.5 g / 10 min or less. The MFR1 of the first polyethylene resin may be 0.1 g / 10 min or more, or 0.3 g / 10 min or more. In this specification, the melt flow rate means a value measured in accordance with JIS K6921-2.

[0027] The thickness of the surface layer 11 is not particularly limited, and can be appropriately determined according to the cost and the application, taking into consideration the suitability of the manufacturing method and the apparatus, and the suitability for lamination with other layers. From a practical viewpoint, the thickness of the surface layer 11 may be 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, or 5 μm or more, or may be 50 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less.

[0028] (Middle class) The intermediate layer 12 is a layer containing a polyethylene resin. Hereinafter, the polyethylene resin constituting the intermediate layer 12 is also referred to as a second polyethylene resin. The content of the second polyethylene resin in the intermediate layer 12 may be 90% by mass or more, 95% by mass or more, or 98% by mass or more based on the total amount of the intermediate layer 12, or may be 100% by mass (an embodiment in which the intermediate layer 12 is substantially composed of the second polyethylene resin). When the intermediate layer 12 is composed of a plurality of polyethylene resins (e.g., a plurality of polyethylene resins having different average molecular weights, densities, etc.), a mixture of the plurality of polyethylene resins is defined as the second polyethylene resin.

[0029] From the viewpoints of wrinkle resistance and excellent processing stability, gas barrier properties that can be more easily maintained even after heat sterilization treatment, and excellent heat resistance, the intermediate layer 12 may be composed of a second polyethylene resin having a density in the following range. The density of the second polyethylene resin is 0.940 g / cm 3 More than 0.945g / cm 3 or more than 0.950g / cm 3 The density of the second polyethylene resin may be 0.980 g / cm or more. 3 Below, 0.975g / cm 3 Below, 0.970g / cm 3 or less than 0.965g / cm 3 It may be the following.

[0030] The composite elastic modulus of the intermediate layer 12 is 1.80 GPa or more and less than 2.50 GPa. By having the composite elastic modulus of the intermediate layer 12 be 1.80 GPa or more and less than 2.50 GPa, wrinkles are less likely to occur in the multilayer polyethylene film 10, and the transparency and gas barrier properties are excellent. The composite elastic modulus of the intermediate layer 12 can be measured by a nanoindentation method, specifically, by the method described in the examples below.

[0031] The composite elastic modulus of the intermediate layer 12 may be 1.90 GPa or more, 2.00 GPa or more, 2.05 GPa or more, 2.10 GPa or more, or 2.15 GPa or more, and may be 2.40 GPa or less, 2.35 GPa or less, or 2.30 GPa or less.

[0032] The melt flow rate MFR2 of the second polyethylene resin at 190°C under a load of 2.16 kg is not particularly limited and can be appropriately adjusted depending on the method for producing the second polyethylene resin. The melt flow rate MFR2 of the second polyethylene resin at 190°C under a load of 2.16 kg may be 5 g / 10 min or less, 3 g / 10 min or less, 2 g / 10 min or less, or 1.5 g / 10 min or less. The MFR2 of the second polyethylene resin may be 0.1 g / 10 min or more, 0.5 g / 10 min or more, or 0.8 g / 10 min or more.

[0033] The thickness of the intermediate layer 12 is not particularly limited, and can be appropriately determined according to the cost and application, taking into consideration the suitability of the manufacturing method and device, and the suitability for lamination with other layers. From a practical standpoint, the thickness of the intermediate layer 12 may be 5 μm or more, 8 μm or more, 10 μm or more, 12 μm or more, or 15 μm or more, or may be 80 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less.

[0034] From the viewpoint of easily maintaining gas barrier properties even after heat sterilization treatment and having excellent heat resistance, the ratio of the thickness of the intermediate layer 12 to the total thickness of the surface layer 11 and the back layer 13 (thickness of intermediate layer / (thickness of surface layer+thickness of back layer)) is 0.5 or more. The ratio of the thickness of the intermediate layer 12 to the total thickness of the surface layer 11 and the back layer 13 may be 1 or more, 1.2 or more, 1.4 or more, or 1.5 or more. The ratio of the thickness of the intermediate layer 12 to the total thickness of the surface layer 11 and the back layer 13 may be 3 or less, 2.5 or less, or 2 or less.

[0035] The greater the thickness of the intermediate layer 12, the better the heat resistance can be realized. The thickness of the intermediate layer 12 may be greater than the thickness of the surface layer 11 and / or the thickness of the back layer 13 from the viewpoint of more easily maintaining the gas barrier property even after heat sterilization treatment and more excellent heat resistance. The thickness of the intermediate layer 12 may be 1 or more times, 1.5 or more times, 2 or more times, 2.5 or more times, or 3 or more times the thickness of the surface layer 11 and / or the back layer 13 from the viewpoint of more easily maintaining the gas barrier property even after heat sterilization treatment and more excellent heat resistance. The thickness of the intermediate layer 12 may be 8 or less times, 7 or less times, 6.5 or less times, or 6 or less times the thickness of the surface layer 11 and / or the back layer 13.

[0036] (Back layer) The back layer 13 is a layer containing a polyethylene resin. Hereinafter, the polyethylene resin constituting the back layer 13 is also referred to as a third polyethylene resin. The content of the third polyethylene resin in the back layer 13 may be 90% by mass or more, 95% by mass or more, or 98% by mass or more based on the total amount of the back layer 13, or may be 100% by mass (an embodiment in which the back layer 13 is substantially composed of the third polyethylene resin). When the back layer 13 is composed of multiple polyethylene resins (e.g., multiple polyethylene resins having different average molecular weights, densities, etc.), a mixture of the multiple polyethylene resins is referred to as the third polyethylene resin.

[0037] The back layer 13 may be made of a third polyethylene resin having a density in the following range from the viewpoints of being less prone to wrinkles, having better processing stability, and being more likely to maintain gas barrier properties and adhesion even after heat sterilization treatment and having better heat resistance. The density of the third polyethylene resin is 0.920 g / cm 3 More than 0.926g / cm 3 More than 0.930g / cm 3 More than 0.935g / cm 3 or more than 0.940g / cm 3 The third polyethylene resin may have a density of 0.970 g / cm or more. 3 Below, 0.965g / cm 3 or less than 0.960g / cm3 The third polyethylene resin may have a density of 0.960 g / cm or less. 3 The above-mentioned conditions can suppress the surface of the multilayer polyethylene film 10 from becoming rough and the generation of resin powder. By suppressing the generation of resin powder, adhesion of resin powder to the surface of the front layer 11 side of the multilayer polyethylene film 10 when the multilayer polyethylene film 10 is wound into a roll can be suppressed, making it easier to achieve excellent gas barrier properties.

[0038] The composite elastic modulus of the back layer 13 is 1.45 GPa or more and less than 1.90 GPa. When the composite elastic modulus of the back layer 13 is 1.45 GPa or more and less than 1.90 GPa, the transparency and gas barrier property of the multilayer polyethylene film 10 are excellent. The composite elastic modulus of the back layer 13 can be measured by a nanoindentation method, specifically, by the method described in the examples below.

[0039] The composite modulus of the backing layer 13 may be 1.50 GPa or more, 1.55 GPa or more, or 1.60 GPa or more, and may be 1.85 GPa or less, 1.80 GPa or less, or 1.75 GPa or less.

[0040] The melt flow rate MFR3 of the third polyethylene resin at 190°C and a load of 2.16 kg is not particularly limited and can be appropriately adjusted depending on the method for producing the third polyethylene resin. The melt flow rate MFR3 of the third polyethylene resin at 190°C and a load of 2.16 kg may be 5 g / 10 min or less, 3 g / 10 min or less, or 1.5 g / 10 min or less. The MFR3 of the third polyethylene resin may be 0.1 g / 10 min or more, or 0.3 g / 10 min or more.

[0041] The thickness of the back layer 13 is not particularly limited, and can be appropriately determined according to the cost and application, taking into consideration the suitability of the manufacturing method and device, and the suitability for lamination with other layers. From a practical standpoint, the thickness of the back layer 13 may be 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, or 5 μm or more, or 50 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less.

[0042] The back layer 13 may have the same configuration as the front layer 11. That is, the multilayer polyethylene film 10 may have a symmetrical structure with respect to the intermediate layer 12. When the multilayer polyethylene film 10 has a symmetrical structure, curling during production of the multilayer polyethylene film 10 can be suppressed, and the multilayer polyethylene film 10 can be produced stably.

[0043] The surface layer 11, the intermediate layer 12, and the back layer 13 may contain a resin other than polyethylene resin as appropriate, as long as the recyclability is not impaired. Examples of such resins include ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, ethylene-(meth)acrylic acid copolymer, homopolypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, propylene-α-olefin copolymer, olefin resins such as polybutene, polyamide, polyethylene vinyl alcohol, polyester, various modifying resins, etc. In addition, each of them may independently contain one or more additives. Examples of additives include crosslinking agents, antioxidants, antiblocking agents, lubricants (slip agents), ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, and pigments.

[0044] The intermediate layer 12 may be a single layer or may be formed of multiple layers. For example, as shown in Fig. 2, the multilayer polyethylene film 30 in the gas barrier film 200 has a surface layer 31, an intermediate layer 32, and a back layer 33, and the intermediate layer 32 has resin layers 32a, 32b, and 32c. In this case, the resin layers 32a, 32b, and 32c all have the same composition. The fact that the intermediate layer 32 has multiple layers can be confirmed by observing the cross section of the multilayer polyethylene film 30 with an optical microscope or an electron microscope.

[0045] The multilayer polyethylene film 10 may have layers other than the three layers of the surface layer 11, the intermediate layer 12, and the back layer 13. For example, as shown in FIG. 3, the multilayer polyethylene film 40 in the gas barrier film 300 has a surface layer 41, an intermediate layer 42, and a back layer 43, a resin layer 44 between the surface layer 41 and the intermediate layer 42, and a resin layer 45 between the intermediate layer 42 and the back layer 43. The resin layer 44 is, for example, a layer containing a polyethylene resin and having a different composition from the surface layer 41 and the intermediate layer 42. The resin layer 45 is, for example, a layer containing a polyethylene resin and having a different composition from the intermediate layer 42 and the back layer 43. The multilayer polyethylene film may have, for example, three layers, five layers, seven layers, or more layers.

[0046] The temperature indicated by the maximum value of the melting peak observed in differential scanning calorimetry of the multilayer polyethylene film 10 is more than 129°C and less than 136°C. The temperature indicated by the maximum value of the melting peak is more than 129°C and less than 136°C, which results in excellent processing stability. When multiple melting peaks are present, the temperatures indicated by the maximum values ​​of all of the melting peaks are within the above range. The temperature indicated by the maximum value of the melting peak means a value measured by the method described in the Examples below.

[0047] From the viewpoints of wrinkle resistance and excellent processing stability, gas barrier properties being more easily maintained even after heat sterilization treatment, and excellent heat resistance, each layer of the multilayer polyethylene film 10 may be composed of a polyethylene resin having a density in the following range. The density of the polyethylene resin is 0.940 g / cm3 More than 0.945g / cm 3 or more than 0.950g / cm 3 The density of the polyethylene resin is 0.980 g / cm or more. 3 Below, 0.975g / cm 3 Below, 0.970g / cm 3 or less than 0.965g / cm 3 It may be the following.

[0048] The method for producing the multilayer polyethylene film 10 is not particularly limited, and the multilayer polyethylene film 10 can be produced by a known method such as an air-cooled inflation method, a water-cooled inflation method, or a T-die casting method. From the viewpoint of versatility, the multilayer polyethylene film 10 may be produced by an inflation method or an air-cooled inflation method. The air-cooled inflation method is a method in which a die having an annular lip called a ring die (or a crosshead die) is installed at the tip of an extruder, and a material is extruded into a tube shape and continuously molded. More specifically, an air hole is installed in the center of the ring die, and compressed air is blown in from the air hole to expand the tube, and the multilayer polyethylene film 10 can be produced by cooling the tube while pulling it with a roller called a pinch roll and winding up the film.

[0049] The obtained multilayer polyethylene film 10 may be subjected to a surface modification treatment to improve suitability for subsequent processes, if necessary. For example, the surface of the multilayer polyethylene film 10 may be modified to improve printability or lamination suitability during lamination. Examples of the modification treatment include treatments that generate functional groups by oxidizing the film surface, such as corona discharge treatment, plasma treatment, and flame treatment, and modification treatments by a wet process that forms an easy-adhesion layer by coating.

[0050] <Gas barrier layer> The gas barrier layer 20 is a layer provided on the multilayer polyethylene film 10 from the viewpoint of improving the gas barrier property against water vapor and oxygen. The gas barrier layer 20 is preferably a layer having transparency. The gas barrier layer 20 has an inorganic oxide layer 21 and a gas barrier coating layer 22. The gas barrier layer 20 may have both the inorganic oxide layer 21 and the gas barrier coating layer 22, or may have only one of the inorganic oxide layer 21 and the gas barrier coating layer 22.

[0051] (Inorganic oxide layer) The inorganic oxide layer 21 contains an inorganic oxide. Examples of inorganic oxides include aluminum oxide, silicon oxide, tin oxide, magnesium oxide, and mixtures thereof. From the viewpoints of more easily maintaining gas barrier properties even after heat sterilization treatment, more excellent heat resistance, and more excellent transparency, the inorganic oxide layer 21 may contain at least one selected from the group consisting of aluminum oxide, silicon oxide, and magnesium oxide.

[0052] The thickness of the inorganic oxide layer 21 may be 5 to 150 nm. If the thickness of the inorganic oxide layer 21 is 5 nm or more, it is easy to form a layer having a uniform and sufficient film thickness, and sufficient gas barrier properties can be realized. If the thickness of the inorganic oxide layer 21 is 150 nm or less, flexibility can be imparted to the inorganic oxide layer 21, and even if an external load such as bending or pulling is applied after the inorganic oxide layer 21 is formed, the inorganic oxide layer 21 can be prevented from cracking. The thickness of the inorganic oxide layer 21 may be 6 nm or more, or 8 nm or more, or 100 nm or less, or 50 nm or less.

[0053] The inorganic oxide layer 21 can be formed by a normal vacuum deposition method. It can also be formed by other thin film formation methods such as sputtering, ion plating, plasma vapor deposition (CVD), etc. The inorganic oxide layer 21 may be formed by the vacuum deposition method from the viewpoint of excellent productivity.

[0054] The heating means for the vacuum deposition method may be any of the electron beam heating method, the resistance heating method, and the induction heating method. The vacuum deposition method may be the electron beam heating method from the viewpoint of a wide range of evaporation material selection. From the viewpoint of improving the adhesion between the multilayer polyethylene film 10 and the inorganic oxide layer 21 and the denseness of the inorganic oxide layer 21, deposition may be performed by a plasma assist method, an ion beam assist method, or the like. From the viewpoint of improving the transparency of the inorganic oxide layer 21, deposition may be performed by reactive deposition.

[0055] (Gas barrier coating layer) The gas barrier coating layer 22 is a layer provided for the purpose of protecting the multilayer polyethylene film 10 or the inorganic oxide layer 21 and complementing the gas barrier property. The gas barrier coating layer 22 may contain a water-soluble polymer and at least one selected from the group consisting of a metal alkoxide, a hydrolysate thereof, and a reaction product thereof. The gas barrier coating layer 22 may contain at least one selected from the group consisting of a silane coupling agent, a hydrolysate thereof, and a reaction product thereof.

[0056] Examples of the water-soluble polymer include polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. The water-soluble polymer may be polyvinyl alcohol (PVA) from the viewpoint of excellent gas barrier properties.

[0057] Examples of metal alkoxides include compounds represented by the following general formula: M(OR 11 ) m (R 12 ) n-m …(1) In the above formula (1), R 11 and R 12 R is each independently a monovalent organic group having 1 to 8 carbon atoms. 11 and R 12may each independently be an alkyl group such as a methyl group or an ethyl group. M represents an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer from 1 to n. 11 and R 12 If there are multiple, R 11 Friends or R 12 They may be the same or different.

[0058] Examples of the metal alkoxide include tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], etc. The metal alkoxide may be tetraethoxysilane or triisopropoxyaluminum from the viewpoint of being relatively stable in an aqueous solvent after hydrolysis.

[0059] Examples of the silane coupling agent include compounds represented by the following general formula: Si(OR 21 ) p (R 22 ) 3-p R 23 …(2) In the above formula (2), R 21 represents an alkyl group such as a methyl group or an ethyl group, and R 22 represents a monovalent organic group such as an alkyl group, an aralkyl group, an aryl group, an alkenyl group, an alkyl group substituted with an acryloxy group, or an alkyl group substituted with a methacryloxy group, and R 23 represents a monovalent organic functional group, and p represents an integer of 1 to 3. 21 or R 22 If there are multiple, R 21 Friends or R 22 R may be the same or different. 23 Examples of the monovalent organic functional group represented by the formula (I) include a monovalent organic functional group containing a glycidyloxy group, an epoxy group, a mercapto group, a hydroxyl group, an amino group, an alkyl group substituted with a halogen atom, and an isocyanate group. The silane coupling agent may be a polymer such as a dimer or trimer of the above-mentioned silane coupling agent.

[0060] Examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane.

[0061] The gas barrier coating layer 22 can be formed by dissolving a water-soluble polymer in water or a water / alcohol mixed solvent, mixing it with a metal alkoxide, a silane coupling agent, or a hydrolyzate thereof to obtain a mixed solution, applying the mixed solution to the surface of the inorganic oxide layer 21 (or the multilayer polyethylene film 10 when the inorganic oxide layer 21 is not present), and drying by heating. Additives such as an isocyanate compound, a dispersant, a stabilizer, a viscosity adjuster, and a colorant may be added to the mixed solution.

[0062] When the water-soluble polymer is PVA, the content of PVA in the mixed solution may be 20 to 50 mass % or 25 to 40 mass % based on the total solid content of the mixed solution. When the content of PVA is 20 mass % or more, it becomes easy to form the gas barrier coating layer 22. When the content of PVA is 50 mass % or less, the gas barrier property is excellent.

[0063] The gas barrier coating layer 22 may be a coating containing a polyvalent metal salt of polycarboxylic acid, which is a reaction product between a carboxy group of a polycarboxylic acid polymer and a polyvalent metal compound (a polyvalent metal salt coating of polycarboxylic acid). The polyvalent metal salt coating of polycarboxylic acid may be formed by applying a mixed solution of a polycarboxylic acid polymer and a polyvalent metal compound to the surface of the inorganic oxide layer 21 (the multilayer polyethylene film 10 when the inorganic oxide layer 21 is not present), and then heating and drying the mixture. Alternatively, a coating liquid mainly composed of a polycarboxylic acid polymer may be applied to the surface of the inorganic oxide layer 21 (the multilayer polyethylene film 10 when the inorganic oxide layer 21 is not present) and dried to form a coating, and then a coating liquid mainly composed of a polyvalent metal compound may be applied to the coating and dried to form a coating, and a crosslinking reaction may be caused between these coatings to form the polyvalent metal salt coating of polycarboxylic acid.

[0064] The polycarboxylic acid polymer is a polymer having two or more carboxyl groups in the molecule. Examples of the polycarboxylic acid polymer include polymers of ethylenically unsaturated carboxylic acids, copolymers of ethylenically unsaturated carboxylic acids and other ethylenically unsaturated monomers, and acidic polysaccharides having carboxyl groups in the molecule, such as alginic acid, carboxymethylcellulose, and pectin.

[0065] Examples of the ethylenically unsaturated carboxylic acid include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Examples of the ethylenically unsaturated monomer copolymerizable with the ethylenically unsaturated carboxylic acid include saturated carboxylic acid vinyl esters such as ethylene, propylene, and vinyl acetate, alkyl acrylates, alkyl methacrylates, alkyl itaconates, vinyl chloride, vinylidene chloride, styrene, acrylamide, and acrylonitrile, etc. The polycarboxylic acid polymer may be one type or two or more types.

[0066] From the viewpoint of excellent gas barrier properties, the ethylenically unsaturated carboxylic acid polymer is preferably a polymer containing a structural unit derived from at least one monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, itaconic acid, fumaric acid, and crotonic acid, and more preferably a polymer containing a structural unit derived from at least one monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid.

[0067] In the ethylenically unsaturated carboxylic acid polymer, the proportion of structural units derived from at least one monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is preferably 80 mol % or more, and more preferably 90 mol % or more, based on the total amount of monomers in the polymer.

[0068] The number average molecular weight of the polycarboxylic acid polymer is preferably 2,000 to 10,000,000, and more preferably 5,000 to 1,000,000. When the number average molecular weight is 2,000 or more, the gas barrier film has sufficient water resistance, and deterioration of gas barrier properties and transparency and whitening caused by moisture can be suppressed. When the number average molecular weight is 10,000,000 or less, the viscosity of the coating liquid when forming the gas barrier coating layer 22 does not become too high, and the coating can be easily formed.

[0069] In the case where a coating liquid mainly composed of a polycarboxylic acid polymer is applied and dried to form a coating, and then a coating liquid mainly composed of a polyvalent metal compound is formed, a part of the carboxyl groups of the polycarboxylic acid polymer may be neutralized in advance with a basic compound. By neutralizing a part of the carboxyl groups of the polycarboxylic acid polymer in advance, the water resistance and heat resistance can be further improved. The basic compound may be at least one basic compound selected from the group consisting of a polyvalent metal compound, a monovalent metal compound, and ammonia. Examples of the polyvalent metal compound include compounds exemplified as polyvalent metal compounds described later. Examples of the monovalent metal compound include sodium hydroxide, potassium hydroxide, and the like.

[0070] The coating liquid containing a polycarboxylic acid polymer as a main component may contain additives such as a crosslinking agent, a curing agent, a leveling agent, an antifoaming agent, an antiblocking agent, an antistatic agent, a dispersing agent, a surfactant, a softener, a stabilizer, a film-forming agent, and a thickener.

[0071] The solvent used in the coating liquid containing a polycarboxylic acid polymer as a main component is preferably an aqueous medium. Examples of the aqueous medium include water, water-soluble or hydrophilic organic solvents, and mixtures thereof. The aqueous medium contains water as a main component. The content of water in the aqueous medium may be 70% by mass or more, or 80% by mass or more. Examples of the water-soluble or hydrophilic organic solvent include alcohols such as methanol, ethanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran; nitriles such as acetonitrile; cellosolves, carbitols, and the like.

[0072] The polyvalent metal compound is not particularly limited as long as it is a compound that reacts with the carboxyl group of the polycarboxylic acid polymer to form a polyvalent metal salt of polycarboxylic acid, and examples thereof include zinc oxide, magnesium oxide, magnesium methoxide, copper oxide, calcium carbonate, etc. The polyvalent metal compound may be zinc oxide from the viewpoint of excellent gas barrier properties. One or more types of polyvalent metal compounds may be used.

[0073] Zinc oxide is an inorganic material having ultraviolet absorbing properties. When zinc oxide is in the form of particles, the average particle size of the zinc oxide particles may be 5 μm or less, 1 μm or less, or 0.1 μm or less, from the viewpoints of gas barrier properties, transparency, and formability of a coating film.

[0074] When a coating film is formed by applying and drying a coating liquid containing a polyvalent metal compound as a main component, the coating liquid may contain, in addition to the polyvalent metal compound (e.g., zinc oxide particles), a solvent, a resin that is soluble or dispersible in the solvent, a dispersant, a softener, a stabilizer, a film-forming agent, a thickener, etc.

[0075] Examples of resins that are soluble or dispersible in a solvent include alkyd resins, melamine resins, acrylic resins, urethane resins, polyester resins, phenolic resins, amino resins, fluororesins, epoxy resins, isocyanate resins, etc. When the coating liquid contains these resins, the coating properties and film-forming properties are improved.

[0076] As the dispersant, an anionic surfactant or a nonionic surfactant can be used. Examples of the surfactant include (poly)carboxylate, alkyl sulfate, alkylbenzene sulfonate, alkylnaphthalene sulfonate, alkyl sulfosuccinate, alkyldiphenyl ether disulfonate, alkyl phosphate, aromatic phosphate, polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, alkyl allyl sulfate, polyoxyethylene alkyl phosphate, sorbitan alkyl ester, glycerin fatty acid ester, sorbitan fatty acid ester, sucrose fatty acid ester, polyethylene glycol fatty acid ester, polyoxyethylene sorbitan alkyl ester, polyoxyethylene alkyl allyl ether, polyoxyethylene derivative, polyoxyethylene sorbitol fatty acid ester, polyoxy fatty acid ester, polyoxyethylene alkylamine, etc. These surfactants may be used alone or in combination.

[0077] When a coating liquid containing a polyvalent metal compound as a main component contains an additive, the mass ratio of the polyvalent metal compound to the additive (polyvalent metal compound:additive) may be 30:70 to 99:1, or 50:50 to 98:2.

[0078] Examples of the solvent used in the coating liquid containing a polyvalent metal compound as a main component include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. From the viewpoint of coating properties, the solvent may be at least one selected from the group consisting of methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water, and from the viewpoint of film-forming properties, it may be at least one selected from the group consisting of methyl alcohol, ethyl alcohol, isopropyl alcohol, and water. One or more solvents may be used.

[0079] Examples of the method for applying the coating liquid include casting, dipping, roll coating, gravure coating, screen printing, reverse coating, spray coating, kit coating, die coating, metalling bar coating, chamber doctor combined coating, and curtain coating.

[0080] The gas barrier coating layer 22 described above can maintain excellent gas barrier properties even after heat sterilization. Therefore, when a laminate in which a sealant layer is provided on the gas barrier film 100 is used as a packaging material for heat sterilization, the packaging material has excellent gas barrier properties even after heat sterilization. In addition, the gas barrier coating layer 22 described above is preferable because it has sufficient transparency, bending resistance, and stretch resistance, and there is no risk of generating harmful substances such as dioxins.

[0081] The thickness of the gas barrier coating layer 22 may be 0.05 μm or more, or 0.1 μm or more, from the viewpoint of excellent gas barrier properties. The thickness of the gas barrier coating layer 22 may be 1 μm or less, or 0.5 μm or less, from the viewpoints of easily forming a uniform coating surface, reducing the load due to drying, and production costs.

[0082] (subbing layer) From the viewpoint of improving the adhesion between the multilayer polyethylene film 10 and the gas barrier layer 20, an undercoat layer (not shown) may be provided between the multilayer polyethylene film 10 and the gas barrier layer 20. By providing an undercoat layer, it becomes easier to maintain the gas barrier properties and adhesion even after heat sterilization treatment.

[0083] The undercoat layer can be formed from a coating liquid containing a resin such as an acrylic resin, an epoxy resin, an acrylic urethane resin, a polyester polyurethane resin, a polyether polyurethane resin, etc. From the viewpoints of heat resistance and interlayer adhesive strength, the undercoat layer may be formed from a coating liquid containing an acrylic urethane resin or a polyester polyurethane resin.

[0084] The method for applying the coating liquid for forming the undercoat layer may be a known coating method, and examples thereof include an immersion method (dipping method), a method using a spray, a coater, a printer, a brush, etc. Examples of the types of coaters and printers used in these methods and the coating methods thereof include gravure coaters such as direct gravure method, reverse gravure method, kiss reverse gravure method, and offset gravure method, reverse roll coaters, microgravure coaters, coaters combined with chamber doctor, air knife coaters, dip coaters, bar coaters, comma coaters, die coaters, etc.

[0085] The method for drying the undercoat layer is not particularly limited, but examples thereof include a method of natural drying, a method of drying in an oven set at a predetermined temperature, and a method using a dryer attached to a coater, such as an arch dryer, a floating dryer, a drum dryer, an infrared dryer, etc. Drying conditions can be appropriately selected depending on the drying method, and for example, in a method of drying in an oven, drying may be performed at 60 to 100°C for about 1 second to 2 minutes.

[0086] The thickness of the undercoat layer may be 0.01 μm or more, 0.03 μm or more, or 0.05 μm or more from the viewpoint of easily obtaining sufficient adhesion between layers, and may be 5 μm or less, 3 μm or less, or 2 μm or less from the viewpoint of excellent gas barrier property.

[0087] <Packaging materials> The gas barrier film 100 can be used as a packaging material for forming a packaging bag. Specifically, the gas barrier film 100 can be provided with a sealant layer to form a laminate, which can be used as a packaging material for flat bags, three-sided bags, palm-shaped bags, gusseted bags, standing pouches, pouches with spouts, pouches with beaks, and the like.

[0088] The gas barrier film 100 can be used as a packaging material as well as a film for electronic devices, a film for solar cells, a film for fuel cells, a substrate film, and the like. EXAMPLES

[0089] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.

[0090] <Polyethylene resin> ·Resin A: Density 0.963g / cm 3 , MFR 1.35g / 10min, DSC melting point 134℃. ·Resin B: Density 0.944g / cm 3 , MFR 0.45g / 10min, DSC melting point 131℃. ·Resin C: Density 0.950g / cm 3 , MFR 1.1g / 10min, DSC melting point 130℃. ·Resin D: Density 0.958g / cm 3 , MFR 1g / 10min, DSC melting point 133℃. ·Resin E: Density 0.960g / cm 3 , MFR 1g / 10min, DSC melting point 135℃. ·Resin F: Density 0.920g / cm 3 , MFR 0.85g / 10min, DSC melting point 124℃. ·Resin G: Density 0.941g / cm 3 , MFR 1.3g / 10min, DSC melting point 129℃. ·Resin H: Density 0.962g / cm 3 , MFR 0.85g / 10min, DSC melting point 134℃. ·Resin I: Density 0.926g / cm 3 , MFR 0.85g / 10min, DSC melting point 123℃.

[0091] <Preparation of polyethylene film> (Examples 1 to 26, Comparative Examples 1 to 11) The resins shown in Tables 1 to 6 constituting the surface layer, intermediate layer, and back layer were respectively fed into an extruder and melt-kneaded at 190°C, after which polyethylene resin was introduced through a three-layer die and a multilayer polyethylene film was produced by an air-cooled inflation method. The overall thickness of the multilayer polyethylene films produced in each Example and Comparative Example was within the range of 25 to 40 μm. The content of polyethylene resin in each of the multilayer polyethylene films produced in each Example and Comparative Example was 90 mass% or more.

[0092] <Preparation of gas barrier film> An undercoat layer, an inorganic oxide layer, and a gas barrier coating layer were formed on the surface of the outer layer side of the multilayer polyethylene film produced in each Example and Comparative Example in the configurations shown in Tables 1 to 6, and a gas barrier film was produced in which the multilayer polyethylene film / undercoat layer / inorganic oxide layer / gas barrier coating layer were laminated in this order. The undercoat layer, adhesive layer, inorganic oxide layer, and gas barrier coating layer were each formed by the methods described below. The polyethylene resin content in the gas barrier films produced in each Example and Comparative Example was 90 mass% or more.

[0093] <Sublayer> Acrylic polyol (DIC Corporation, Acrydic CL-1000) and an isocyanate compound (Tosoh Corporation, TDI type curing agent Coronate 2030) were mixed in a solid content mass ratio of 6:4. Ethyl acetate was then added to dilute the mixture so that the solid content was 2 mass%, to obtain a coating liquid for forming an undercoat layer. After one-sided corona treatment was performed on the surface of the outer layer side of the multilayer polyethylene film of each Example and Comparative Example, the coating liquid for forming the undercoat layer was applied to the corona-treated surface using a gravure printing machine to form a coating film, and the coating film was dried in a 60°C oven for 10 seconds to form an undercoat layer with a thickness of 0.1 μm.

[0094] <Inorganic oxide layer> When the inorganic oxide was silicon oxide, a transparent inorganic oxide layer (silicon oxide film) made of silicon oxide with a thickness of 30 nm was formed using a vacuum deposition apparatus using an electron beam heating method. The silicon oxide film had an O / Si ratio of 1.8. When the inorganic oxide was aluminum oxide, a transparent inorganic oxide layer (aluminum oxide film) made of aluminum oxide with a thickness of 15 nm was formed using a vacuum deposition apparatus using an electron beam heating method. The aluminum oxide film had an O / Al ratio of 1.5.

[0095] <Gas barrier coating layer> (Organic-inorganic composite film) An aqueous solution of polyvinyl alcohol resin (PVA, Kuraray Co., Ltd. Poval PVA-105, saponification degree 98-99%, polymerization degree 500), tetraethoxysilane (TEOS), and γ-glycidoxypropyltrimethoxysilane (GPTMS, Shin-Etsu Chemical Co., Ltd. KBM-403) was prepared by hydrolyzing them with 0.02 mol / L hydrochloric acid. Next, the three aqueous solutions were mixed so that the mass ratio of PVA, TEOS, and GPTMS before hydrolysis was 40:50:10, which was the mass ratio of PVA:TEOS:GPTMS before hydrolysis. Next, the mixed aqueous solution was diluted with isopropyl alcohol so that the mass ratio of water to isopropyl alcohol in the mixed aqueous solution was 90:10, and a coating liquid for forming an organic-inorganic composite coating (solid content: 5 mass%) was obtained. A mixed liquid for an organic-inorganic composite coating, described below, was applied onto the inorganic oxide layer using a gravure printer to form a coating film, and the coating film was dried in an oven at 60°C for 10 seconds to form a gas barrier coating layer consisting of an organic-inorganic composite coating film having a thickness of 0.3 μm.

[0096] (Polycarboxylic acid polyvalent metal salt coating) 20 parts by mass of an aqueous polyacrylic acid solution (Aron A-10H, manufactured by Toagosei Co., Ltd., number average molecular weight 200,000, solid content concentration 25% by mass) was diluted with 58.9 parts by mass of distilled water. Next, 0.44 parts by mass of aminopropyltrimethoxysilane (APTMS, manufactured by Aldrich Co.) was added and stirred to obtain a uniform mixed solution for coating A, the main component of which was a polycarboxylic acid polymer. 100 parts by mass of an aqueous dispersion of zinc oxide particles (ZE143, manufactured by Sumitomo Osaka Cement Co., Ltd.) and 2 parts by mass of a hardener (Liofol HAERTER UR 5889-21, manufactured by Henkel) were mixed to obtain a mixed solution for coating B containing a polyvalent metal compound as a main component. A coating film was formed on the inorganic oxide layer by applying the below-described mixed solution for coating film A using a gravure printer, and then dried in an oven at 60°C for 10 seconds to form a coating film A having a thickness of 0.2 μm. Further, a coating film was formed by applying the mixed solution for coating film B using a gravure printer, and then dried in an oven at 60°C for 10 seconds to form a coating film B having a thickness of 0.2 μm. This resulted in the formation of an oxygen barrier coating film consisting of a polyvalent metal salt coating of polycarboxylic acid.

[0097] <Adhesive layer> (Urethane adhesive) A urethane adhesive was obtained by mixing 100 parts by mass of Takelac A525 (manufactured by Mitsui Chemicals), 11 parts by mass of Takenate A52 (manufactured by Mitsui Chemicals), and 84 parts by mass of ethyl acetate.

[0098] (Epoxy adhesive) An epoxy-based adhesive was obtained by mixing 23 parts by mass of a solvent made by mixing ethyl acetate and methanol in a mass ratio of 1:1 with 16 parts by mass of Maxieve C93T (manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 5 parts by mass of Maxieve M-100 (manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0099] <Composite Elastic Modulus> The multilayer polyethylene film was embedded in visible light curable resin D-800. Next, the multilayer polyethylene film was cut perpendicular to the lamination direction using an ultramicrotome Leica EM UC7 and a diamond knife Microstar LH. The resulting cross section was finished with a cutting thickness of 100 nm and a cutting speed of 1 mm / s to prepare a measurement sample. For the measurement, a Hysitron TI-Premier (product name) manufactured by Bruker Japan Co., Ltd. was used as the measuring device, and a Berkovich type diamond indenter manufactured by Bruker Japan Co., Ltd. was used as the indenter. The measurement conditions were as follows. Temperature: normal temperature (25℃). Mode: Load control mode. Pressing and unloading: Pressing was performed up to a load of 15 μN at a pressing speed of 1.5 μN / s, the maximum load was maintained for 5 seconds, and then the load was removed at a speed of 1.5 μN / s. Measurement location: Using the shape measurement function of the measuring device that scans the sample surface with an indenter, a shape image of the cross section of the sample is obtained, and 20 points are specified on the cross section of the sample from the shape image at intervals of 1 μm or more. When calculating the composite elastic modulus, the relationship between the contact depth and the contact projection area between the indenter and the sample was calibrated in advance using fused quartz as a standard sample. After that, the unloading curve in the 60-95% range of the maximum load at the time of unloading was analyzed by the Oliver-Pharr method, and the composite elastic modulus of the measured sample was calculated. The measurement results are shown in Tables 1 to 6.

[0100] <Melting peak temperature> The prepared multilayer polyethylene film was subjected to differential scanning calorimetry in accordance with JIS K7121-1987 using a differential scanning calorimeter (manufactured by Hitachi, Ltd., product name DSC7020) at a measurement temperature of 20 to 200°C and a heating rate of 10°C / min, and the temperature of the maximum value of the melting peak of the obtained curve was read. The results are shown in Tables 1 to 6. Note that if the maximum value of the melting peak does not exist within the range of more than 129°C and less than 136°C, it is indicated in the table as "-".

[0101] [evaluation] <Processing stability> After forming the gas barrier coating layer (for the examples in which the gas barrier coating layer was not formed and the comparative examples, after forming the inorganic oxide layer), the appearance of the gas barrier film was visually confirmed, and the processing stability was evaluated based on the following evaluation criteria. The evaluation results are shown in Tables 1 to 6. A: No wrinkles were observed on the exterior of the gas barrier film. B: Slight wrinkles were observed on the exterior of the gas barrier film. C: Numerous wrinkles were observed on the exterior of the gas barrier film.

[0102] <Transparency> The haze of the produced multilayer polyethylene film was measured using a haze meter (NDH-20, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7136, and the transparency was evaluated based on the following evaluation criteria. The evaluation results are shown in Tables 1 to 6. A: Haze is less than 20% B: Haze is between 20% and 35% C: Haze is 35% or more

[0103] <Oxygen barrier properties> The gas barrier films produced in each Example and Comparative Example were dry laminated with the above-mentioned urethane adhesive or the above-mentioned gas barrier adhesive using a multi-coater TM-MC (manufactured by HIRANO TECSEED), and then cured at 40°C for 3 days to form an adhesive layer. After curing, LLDPE (polyethylene film, manufactured by Mitsui Chemicals Tohcello, TUX MC-S, thickness 60 μm) was attached to the adhesive layer to produce a laminate in which gas barrier film / adhesive / LLDPE were laminated in this order. The oxygen permeability (cm2) of the produced laminate was measured using an oxygen permeability measuring device (product name OXTRAN-2 / 20, manufactured by MOCON) in an atmosphere of 30°C and 70% RH in accordance with JIS K-7126-2 Method B. 3 / (m 2 The oxygen barrier properties were evaluated based on the following criteria. The evaluation results are shown in Tables 1 to 6. A+: Oxygen permeability is 2cm 3 / (m 2 ·day·atm). A: Oxygen permeability is 2cm 3 / (m 2 ·day · atm) or more, 5cm 3 / (m 2 ·day·atm). A-: Oxygen permeability is 5cm 3 / (m 2 ·day · atm) or more, 10cm 3 / (m 2 ·day·atm). B+: Oxygen permeability is 10cm 3 / (m 2 ·day · atm) or more, 20cm 3 / (m 2 ·day·atm). B: Oxygen permeability is 20cm 3 / (m 2 ·day · atm) or more, 50cm 3 / (m 2 ·day·atm). B-: Oxygen permeability is 50cm 3 / (m 2 ·day·atm) or more.

[0104] <Oxygen barrier properties after boiling treatment> The prepared laminate was cut into two pieces measuring 15 cm x 10 cm, and the two cut laminates were stacked so that the sealant layers faced each other, and three sides were impulse sealed to form a pouch. 150 mL of water was placed in the pouch as the contents, and the remaining side was impulse sealed to prepare a pouch (packaging bag) with four sides sealed. The prepared pouch was boiled at 95°C for 30 minutes in a boiling treatment device. After the boiling treatment, the pouch was opened to remove the contents, and thoroughly dried, and then the oxygen permeability was measured by the above-mentioned method to evaluate the oxygen barrier property. The evaluation results are shown in Tables 1 to 6.

[0105] [Table 1]

[0106] [Table 2]

[0107] [Table 3]

[0108] [Table 4]

[0109] [Table 5]

[0110] [Table 6] [Explanation of symbols]

[0111] 10, 30, 40...multilayer polyethylene film; 11, 31, 41...surface layer; 12, 32, 42...intermediate layer; 13, 33, 43...back layer; 20...gas barrier layer; 21...inorganic oxide layer; 22...gas barrier coating layer; 100, 200, 300...gas barrier film.

Claims

1. A gas barrier film having a laminated structure including a multilayer polyethylene film and a gas barrier layer, the multilayer polyethylene film has a surface layer, an intermediate layer, and a back layer in this order, the surface layer being provided between the intermediate layer and the gas barrier layer; The surface layer has a thickness of 0.926 g / cm 3 It is made of medium density polyethylene resin or high density polyethylene resin having a density of or above, The composite elastic modulus of the surface layer and the back layer is 1.45 GPa or more and less than 1.90 GPa, and the composite elastic modulus of the intermediate layer is 1.80 GPa or more and less than 2.50 GPa, The ratio of the thickness of the intermediate layer to the total thickness of the front layer and the back layer is 0.5 or more; The temperature at which the maximum melting peak is observed in differential scanning calorimetry of the multilayer polyethylene film is more than 129° C. and less than 136° C.; The gas barrier film, wherein the gas barrier layer comprises at least one of an inorganic oxide layer and a gas barrier coating layer.

2. The density of the multilayer polyethylene film is 0.940 g / cm 3 The gas barrier film according to claim 1 .

3. the gas barrier layer has the inorganic oxide layer, The gas barrier film according to claim 1 , wherein the inorganic oxide layer contains at least one of aluminum oxide and silicon oxide.

4. the gas barrier layer has the gas barrier coating layer, 2. The gas barrier film according to claim 1, wherein the gas barrier coating layer comprises a water-soluble polymer and at least one member selected from the group consisting of metal alkoxides, their hydrolysates, and reaction products thereof.

5. the gas barrier layer has the gas barrier coating layer, 2. The gas barrier film according to claim 1, wherein the gas barrier coating layer comprises at least one member selected from the group consisting of a silane coupling agent, a hydrolysate thereof, and a reaction product thereof.

6. the gas barrier layer has the gas barrier coating layer, The gas barrier film according to claim 1 , wherein the gas barrier coating layer comprises a polyvalent metal salt of a carboxylic acid.

Citation Information

Patent Citations

  • Polyethylene multilayered film to be metallized

    JP1994270357A

  • Aluminum vapor deposited polyethylene film and method of manufacturing the same

    JP2001179878A

  • Barrier laminated film

    JP2013022918A

  • Packaging material for paper container

    JP2015224063A

  • Film, laminate film and package composed of laminate film

    JP2018024213A